PERSEPSI SISWA TERHADAP USAHA ORANG TUA DALAM PENANAMAN NILAI KARAKTER DI SMP NEGERI 2 KECAMATAN BANDAR SEI KIJANG KABUPATEN PELALAWAN - Jumiana, Ana Jumiana Ana; Bahar, Aswandi Bahar Aswandi; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problems of this study is how high the efforts of parents to instill character values in children at SMP Negeri 2 Bandar Sei Kijang Pelalawan. The purpose of this study was to determine the level of effort of parents in instilling the value of character in children in the District of SMP Negeri 2 Bandar Sei Kijang Pelalawan. The benefits of this research can provide additional information to the parents about the efforts of parents to instill character values. This is a descriptive study with a quantitative approach. The population is 50 people. The samples in this study using the technique of saturated sample. The instrument used in this study was a questionnaire containing 67 items statements about students' perception of the parents in planting value character in SMP Negeri 2 Bandar Sei Kijang Pelalawan, with indicator 1) religious, 2) honest, 3) discipline, 4) appreciate the achievement, 5) loved to read, and 3) responsibility. Alternative answers each item has a statement strongly agree categories (SS) was scored 5, agrees (S) was given a score of 4, less amenable (KS) was given a score of 3, disagree (TS) was given a score of 2, and strongly disagree (STS) given a score of 1. The survey results revealed that students' perceptions of their parents in planting the value of the character in SMP Negeri 2 Bandar Sei Pelalawan Kijang high. This is evidenced from the exposure data summary are: (1) Religious with a choice of answers strongly agree (SS) and agree (s) obtained percentage score of 64.21%, (2) To be honest with choice answers strongly agree (SS) and agree (s) is obtained percentage score of 81.99%, (3) the discipline with a choice of answers strongly agree (SS) and agree (s) obtained percentage score of 76.1%, (4) the achievements by the choice of answers strongly agree (SS) and agree (s) percentage score of 63.325% was obtained, (5) likes to read the answer choices strongly agree (SS) and agree (s) obtained a score of percentage 62.46%, and (6) the responsibility of the answer choices strongly agree (SS) and agree (S ) earned a score of 66.105% percentage. This means that parents have to instill character values to their children properly.Keywords: Perception, Enterprises parents, Planting the value of character